Relationship between knowledge level and smoking habit behavior with the incidence of pulmonary tuberculosis patients: A cross-sectional study - Nurhayati, Nurhayati; Febrianti, Febrianti (Science Center Group, 2024)
Background: Pulmonary tuberculosis remains one of the leading infectious diseases contributing to the global health burden. Behavioral factors such as smoking habits and inadequate knowledge about the disease may increase individual susceptibility to Mycobacterium tuberculosis infection. Understanding the relationship between knowledge level and smoking behavior with pulmonary tuberculosis incidence is important to strengthen behavior-based prevention strategies in tuberculosis control. Objective: This study aimed to analyze the relationship between knowledge level and smoking habit behavior with the incidence of pulmonary tuberculosis patients. Methods: This study employed a quantitative descriptive design with a cross-sectional approach. The sample consisted of 32 pulmonary tuberculosis patients selected using an accidental sampling technique. The independent variables were knowledge level and smoking habit behavior, while the dependent variable was pulmonary tuberculosis incidence. Data were collected using structured questionnaires and checklists developed by the researchers. Data analysis was performed using the Chi-square test with SPSS software at a significance level of α = 0.05. Results: The results showed that among 32 respondents, 43.8% were diagnosed with pulmonary tuberculosis. Most respondents had poor knowledge levels (59.4%) and unfavorable smoking behaviors (59.4%). Bivariate analysis indicated a significant relationship between knowledge level and pulmonary tuberculosis incidence (p = 0.020). Smoking habit behavior also demonstrated a significant association with pulmonary tuberculosis incidence (p = 0.020). Conclusion: Knowledge level and smoking habit behavior are significantly associated with pulmonary tuberculosis incidence. Strengthening community knowledge and implementing smoking cessation interventions are important components in pulmonary tuberculosis prevention and control programs.